Influence of comorbidity on patients evolution with upper gastrointestinal bleeding from peptic ulcer - Mirtha Infante Velázquez; Yusimik Román Martínez; Rebeca Winograd Lay; Juan Yerandy Ramos Contreras; Dorelys Rodriguez Alvarez; Ernesto Corujo Arias (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Despite the endoscopic therapy advances, morbidity and mortality of patients with gastrointestinal bleeding are high. Objective: To determine if there is relationship between comorbidity and its severity with short-term developments in the ulcerative patient presenting acute upper gastrointestinal bleeding episode. Material and Methods: We performed an observational, descriptive, prospective and longitudinal research in the Central Military Hospital "Dr. Luis Díaz Soto" between September 2013 and March 2015. 103 patients that bled due to peptic ulcer were included. The bleeding stigmas were identified by means of Forrest classification, correspondently; endoscopic therapy was applied and assessed using the Charlson Comorbidity Index. Comparisons between the groups with and without comorbidity and gravely ill regarding treatment results, rebleeding, surgery and mortality were made. Results: Male patients predominated (69.9%) and older than 60 years old (62. 7±17. 8 years). 58.3% presented comorbidity. The condition most prevalent was ischemic heart disease (21.4%). Among patients with co-morbidity existed higher probability of finding during endoscopy of acute bleeding stigmata or recent bleeding (RR = 1 2; IC 95% = 0.48-2.98). The rebleeding risk was higher among those who had moderate comorbidity (RR = 1. 5; 95% CI: 0.25-8.97; (p = 0.006). The need for surgery was not related to co-morbidity. Mortality was precocious (21.4%) and was related to the coexistence of hepatic cirrhosis. Conclusions: The greater influence of co-morbid diseases occurs on bleeding relapse and mortality.  Keywords: Upper gastrointestinal bleeding, peptic ulcer, comorbidity,Charlson Comorbidity Index, endoscopic therapy.